Healthy body as a normative model in the perceptions of student youth - N. L. Antonova; S. B. Abramova; V. R. Lopatina (Образование и наука)
Introduction. The relevance of the study is due to the need to analyse the ideas of normative body image in the minds of students in the context of current social changes, including those related to the consequences of the Coronavirus pandemic, as well as updating ideas about the properties and characteristics of the body, its ability to function effectively in modern conditions.Aim. The article aimed to analyse students’ ideas about the normative body and to determine its model that is relevant in modern reality.Methodology and research methods. The theoretical and methodological basis of the article is a complex of sociological concepts of the body and corporality. An online survey method was used to collect empirical data. The sample consisted of 380 students living in large cities of the Sverdlovsk Region: Ekaterinburg, Nizhny Tagil and Kamensk-Uralsky. The results obtained were processed using the SPSS statistical data processing software. In order to deepen the data obtained, projective methods were applied – the method of an unfinished sentence and the drawing method.Results and scientific novelty. The survey materials showed that students’ ideas about the normative body correspond to traditional body stereotypes: attractiveness and beauty are attributed to the female body, and working capacity and endurance are attributed to the male body. However, when using projective methods, the rhetoric of corporality shifted into the normative model of a healthy body. The analysis of body care practices indicates the presence of a core, including physical activity and balanced nutrition, which students use to achieve a healthy body as a body that is aesthetically attractive and functionally hardy. Highly appreciating satisfaction with their body, the younger generation strives for a normative model of a healthy body, which gives a sense of comfort to its wearer and allows the realisation of a wide range of needs and interests. In the post-pandemic context, students more often, compared to the pre-pandemic situation, began to include personal hygiene, mental health care, and physical activity in their daily practices.Practical significance. Empirical data contribute to the understanding of students’ ideas about the normative body, the motives for its construction and care for it, and can also serve as the basis for the development of recommendations and programmes for the formation of students’ culture of a healthy body in terms of physical and mental characteristics.